Investing in the Buddhist Circuit : Enhancing the Spiritual, Environmental, Social, and Economic Value of the Places Visited by the Buddha in Bihar and Uttar Pradesh, India - International Finance Corporation (World Bank, Washington, DC, 2017)
India is one of the world’s great reservoirs of history, cultures, philosophies, and religions. The Buddhist circuit is a route that follows in the footsteps of the Buddha from Lumbini in Nepal where he was born, through Bihar in India where he attained enlightenment, to Sarnath and Kushinagar in Uttar Pradesh in India, where he gave his first teachings and died. The Buddhist circuit is an important pilgrimage destination for the 450 million practicing Buddhists as well as travelers interested in history, culture, or religion. Investing in the Buddhist Circuit is the result of first-time collaboration between the Government of India’s Ministry of Tourism, the State Governments of Bihar and Uttar Pradesh, the private sector, Buddhist monasteries and sects, and the World Bank Group. The work was led by the International Finance Corporation (IFC), a member of the World Bank Group. Extensive on-the-ground data collection, consultations, and analysis were conducted. The outcome is a framework for public and private sector investment that secures and enhances the experience of the sites while unleashing the full job creation potential of tourist spending at the towns and sites, and along the Buddhist circuit. The strategy outlined in this document seeks to grow the economic impact of tourism along the Buddhist circuit by attracting higher-spending tourists and linking them to local goods and service providers. This strategy recognizes that both public and private sector investment is required to drive demand and improve quality of experience while respecting, preserving, and enhancing the religious value and significance of the sites. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.